Textual Writing and the Authority of Intertextuality - Othman, Nawzat A.; Abdulkarim, Abduqader N.; Miro, Rafiq S. (Humanities Journal of University of Zakho, 2018)
Intertextuality is mainly an existence, transformation, the embodiment of an ancient and a modern text to the inside of a modern complex text. The ancient texts become the hidden and shown parts in the basic modern text. This study attempts to give importance to the knowledge of how to write the text and the impact of Intertextuality on the action of construction as well as working on the stages of structures and the range of Intertextuality’s effect. The study briefly starts to demonstrate the intertextuality; it also shows the stages of writing the text and of the way of how to compose each stage. Finally, the study is concluded with having several results and conclusions.